FTIR Spectroscopy for Gypsum after Treatment with Steam Pressure - Al-Jobouri, H A (Al-Nahrain Journal of Science, 2011)
The effect of 2 bar steam pressure was studied on the Mm and Ms mineral sources of calcium sulphate dihydrate CaSO4.2H2O with and without milling respectively, which is than compared with autoclave calcium sulphate hemihydrate Mα ; α-hemihydrate, and CaSO4.2H2O annular; Ma by using FTIR spectroscopy technique at a wave number range 500-4000 Cm-1. The transmittance ratio; T*-ratio = [ (T660/T1620) x 100] for Mα, Ma, and Mm, was 96.96 %, 95.26% and 72.47% respectively compared with 82.70% at Mm which is treated with 2 bar steam pressure; MP2. The transmittance ratio; [T*-ratio] decreased in Ms after the steam pressure (1-6 bar) treatment. The effect of time 0.5 to 2.5 h on passing under 6 bar steam pressure on Mm displays the wave numbers at the range 2000 - 2500 Cm-1 which nearly reaching the same to spectrum of Mα. FTIR– spectrum at the range 500-1500 Cm-1 for AL-ahliyah gypsum ( gypsum-Iraqi plaster ); Mh which is calcium sulphate dihydrate heated in open vessel and Mm on treatment by 6 bar steam pressure for 2.5 h; MP6 was studies the destruction of this spectrum range comparing with Mα. The disadvantage of steam pressure on gypsum was observed by stretching of OH-group at the rang 3000-4000 Cm-1 in Mm, where the increasing of steam pressure in MP2 and MP6 caused in disappearing the wave numbers of 3609 and 3553 Cm-1 compared with the wave numbers appearing in Mα and Mh. This study showed the steam pressure may be used as a good parameter to change Mm to Mα which equivalent to the physical properties of dental material.